Sex Differences in Gut Microbial Development of Preterm Infant Twins in Early Life: A Longitudinal Analysis - Chen, Jie; Li, Hongfei; Hird, Sarah M.; Chen, Ming-Hui; Xu, Wanli; Maas, Kendra; Cong, Xiaomei (Frontiers in Cellular and Infection Microbiology, 2021)
Infant gut microbiota plays a vital role in immune response, mediates neurobehavioral development and health maintenance. Studies of twins’ gut microbiota found that gut microbiota composition and diversity tend to be mature and stable with increasing postnatal age (PNA). Preterm infant gut microbiome shifts dramatically when they were staying in the neonatal intensive care unit (NICU). Compositions and shifting characteristics of gut microbiota among neonatal preterm twins and triplets during their early life are still unknown, which impedes a better understanding of the mechanism underpinning neurobehavioral development and precise intervention/health of preterm neonates. This longitudinal cohort study used a twins/triplets design to investigate the interaction of genetic (e.g., male vs. female) and environmental factors influencing the development of the gut microbiome in early life. We included 39 preterm infants, 12 were Female twins/triplets (Female T/T) including 3 twins pairs and 2 triplets, 12 were male twins (Male T) including 6 twins pairs, and 15 were mixed-sex twins/triplets (Mix T/T) including 6 twins pairs and 1 triplet (8 females and 7 males) during the first four weeks of NICU stay. Weekly gut microbiota patterns between females and males were compared by linear discriminant analysis (LDA) effect size (LEfSe). Metagenomics function of gut microbiota was predicted by using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt). Weekly function (KEGG pathways) differences between females and males were detected by using Statistical Analysis of Metagenomic Profiles (STAMP). Results found that female pairs and male pairs were significantly different in gut microbiome diversity, compositions, and predicted metabolic profiles, importantly, females and males were also significantly dissimilar within their co-twin/triplet pairs of the mixed-sex group, infants of co-twins/triplets shared more similar features than un-related infants from different twins’ pair. Future research developing personalized interventions for vulnerable high-risk infants should consider sex, and the interaction of sex and environmental factors.